Strategi Guru Fiqih dalam Manajemen Kelas untuk Meningkatkan Kedisiplinan dan Konsentrasi Peserta Didik di MTsN 6 Agam - Apulina Br Ginting; Fenny Ayu Monia (Lembaga Yasin AlSys, 2026)
Although classroom management has been a concern in various educational studies, research that specifically discusses teachers’ strategies in managing classrooms to improve students’ discipline and concentration in Fiqh learning at madrasahs remains limited. This study aims to analyze the strategies of Fiqh teachers in classroom management to improve students’ discipline and concentration, identify the obstacles faced by teachers in its implementation, and explain the efforts made to overcome those obstacles. This study employed a qualitative approach with a field research design, involving one Fiqh teacher as the key informant and several eighth-grade students as supporting informants selected through purposive sampling. Data were collected through observation, structured interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the Fiqh teacher implemented several classroom management strategies, namely arranging students’ seating, applying classroom rules, using varied learning methods such as lectures, question-and-answer, and discussion, as well as supervision and a personal approach to students. These strategies proved capable of creating a more orderly and conducive learning atmosphere, thereby improving students’ learning discipline and concentration. These findings emphasize the importance of implementing effective classroom management strategies in creating a conducive learning environment, increasing students’ engagement in the learning process, and enriching classroom management studies in the context of Islamic Religious Education at madrasahs. The implications of this study indicate that teachers and educational institutions need to develop more adaptive and effective classroom management strategies, while also opening opportunities for further research on the relationship between classroom management and learning motivation, student character, and the learning environment at madrasahs.